2001
DOI: 10.1079/pns200198
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in adipose tissue in human disease

Abstract: Redistribution of white adipose tissue is a long-term symptom of several chronic diseases. Although the roles of adipocytes in acute illness have been thoroughly studied, how or why short-term responses of adipose tissue to disease sometimes produce long-term redistribution, and the causal relationship between the anatomical changes and the associated metabolic syndromes are poorly understood. The present paper reviews explanations for the redistribution of adipose tissue after infection with HIV, and in Crohn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 68 publications
4
35
0
1
Order By: Relevance
“…Although the influence of the increased TNFα and PGE 2 plasma levels, characteristic of the tumour-bearing state (Tisdale 2004;Lieb 2001), must not be discarded, the fact that the infiltrating macrophages actively produce these factors and are present at an early stage of cachexia in the adipose tissue strongly suggests they may play a role in the decreased leptin tissue concentration, since the elevation of both circulating PGE 2 and TNFα is known to be time dependent (McCarthy 2003). The importance of local modulation of adipose tissue metabolism and function in health and disease is stressed by Pond (2001) Taken together, the results point out to a possible modulation of leptin secretion in three different adipose tissue depots of cachectic rats by factors produced by the macrophage infiltrate, which was present in all the analysed samples. The results provide further evidence to the current view of cachexia as a chronic inflammatory syndrome and for local modulation of adipose tissue physiology under the syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…Although the influence of the increased TNFα and PGE 2 plasma levels, characteristic of the tumour-bearing state (Tisdale 2004;Lieb 2001), must not be discarded, the fact that the infiltrating macrophages actively produce these factors and are present at an early stage of cachexia in the adipose tissue strongly suggests they may play a role in the decreased leptin tissue concentration, since the elevation of both circulating PGE 2 and TNFα is known to be time dependent (McCarthy 2003). The importance of local modulation of adipose tissue metabolism and function in health and disease is stressed by Pond (2001) Taken together, the results point out to a possible modulation of leptin secretion in three different adipose tissue depots of cachectic rats by factors produced by the macrophage infiltrate, which was present in all the analysed samples. The results provide further evidence to the current view of cachexia as a chronic inflammatory syndrome and for local modulation of adipose tissue physiology under the syndrome.…”
Section: Discussionmentioning
confidence: 98%
“…Many of these findings of a protective factor of overweight or low-grade obesity (BMIs of 30-35) apply to morbidity among people with diabetes, stroke, and acute coronary syndrome (Curtis, 2005), and a recent study found that obese and overweight patients had better nutritional status than normal or underweight patients (Casas-Varas et al, 2012). Some research suggests that increased fat reserves might offer some benefit in times of illness or injury (Klein et al, 2007) and omental fat (abdominal fat), which is increased among obese persons (Smith et al, 2001) is believed to have some beneficial immune-modulating effects in times of biological stress or trauma (Pond, 2001). The protective benefits of obesity may be even more pronounced for older adults in terms of bone breaks or other fall-related injuries (Oreopoulos, Kalantar-Zadeh, Sharma, & Fonarow, 2009).…”
Section: Obesity Paradoxmentioning
confidence: 97%
“…Possible mechanisms include alterations of membrane structure and composition (Raulin, 2002). Lipid-rich diets characterised by a very low n-3:n-6 fatty acids ratio are common in developed countries, and are implicated in various abnormalities of immune function (Calder, 2001), including the increasing incidence of Crohn's disease, which is also characterised by an anomalous growth of mesenteric adipose tissue (Pond, 2001). Such diets increase the abundance of DC in intra-abdominal and peripheral adipose depots that incorporate lymphoid tissue (Table 2).…”
Section: Discussionmentioning
confidence: 99%